ICAM-1 Targeted Drug Combination Nanoparticles Enhanced Gemcitabine-Paclitaxel Exposure and Breast Cancer Suppression in Mouse Models - Linxi Zhu; Qingxin Mu; Jesse Yu; James I. Griffin; Xiaolin Xu; Rodney J. Y. Ho (MDPI AG, 2021)
Despite the availability of molecularly targeted treatments such as antibodies and small molecules for human epidermal growth factor receptor 2 (HER2), hormone receptor (HR), and programmed death-ligand 1 (PD-L1), limited treatment options are available for advanced metastatic breast cancer (MBC), which constitutes ~90% mortality. Many of these monotherapies often lead to drug resistance. Novel MBC-targeted drug-combination therapeutic approaches that may reduce resistance are urgently needed. We investigated intercellular adhesion molecule-1 (ICAM-1), which is abundant in MBC, as a potential target to co-localize two current drug combinations, gemcitabine (G) and paclitaxel (T), assembled in a novel drug-combination nanoparticle (GT DcNP) form. With an ICAM-1-binding peptide (referred to as LFA1-P) coated on GT DcNPs, we evaluated the role of the LFA1-P density in breast cancer cell localization in vitro and in vivo. We found that 1-2% LFA1-P peptide incorporated on GT DcNPs provided optimal cancer cell binding in vitro with ~4× enhancement compared to non-peptide GT DcNPs. The in vivo probing of GT DcNPs labeled with a near-infrared marker, indocyanine green, in mice by bio-imaging and G and T analyses indicated LFA1-P enhanced drug and GT DcNP localization in breast cancer cells. The target/healthy tissue (lung/gastrointestinal (GI)) ratio of particles increased by ~60× compared to the non-ligand control. Collectively, these data indicated that LFA1 on GT DcNPs may provide ICAM-1-targeted G and T drug combination delivery to advancing MBC cells found in lung tissues. As ICAM-1 is generally expressed even in breast cancers that are triple-negative phenotypes, which are unresponsive to inhibitors of nuclear receptors or HER2/estrogen receptor (ER) agents, ICAM-1-targeted LFA1-P-coated GT DcNPs should be considered for clinical development to improve therapeutic outcomes of MBCs.